Patient-reported outcomes and quality of life after pelvic organ prolapse surgery in Indonesia - Hakim, Surahman; Hadinata, Valencia; Wiguna, Igor Ian; Tanoto, Kevin; Amelia, Safira; Kadarusman, Adib Kamil Putra (Medical Journal of Indonesia, 2026)
BACKGROUND Pelvic organ prolapse (POP) is a common condition in older women that significantly impacts quality of life (QoL). Traditional surgical success measures primarily focus on anatomical outcomes, but patient-reported outcomes provide offer a more comprehensive assessment of symptom relief and overall well-being. This study aimed to evaluate patient-reported outcomes and QoL with the Pelvic Floor Disability Index (PFDI-20) and Pelvic Floor Impact Questionnaire (PFIQ-7) following POP surgery. METHODS This cross-sectional study analyzed secondary data from medical records and patient interviews at Cipto Mangunkusumo Hospital, Jakarta. Patients diagnosed with POP who underwent surgery were followed up at 1, 3, 6, and 12 months postoperatively. PFDI-20 and PFIQ-7 scores were used to assess symptom impact and QoL. RESULTS Among 34 patients, the most common surgical method was total vaginal hysterectomy (79%), followed by colpocleisis (59%), and sacrospinous hysteropexy (6%). Postoperative PFDI-20 scores showed 76% of patients experienced minimal to no impact, while PFIQ-7 scores indicated 91% reported minimal to no impact on their QoL. 2 patients reported moderate impact, particularly in the urinary domain. No patients experienced severe or very severe impairment at any follow-up interval. CONCLUSIONS Incorporating patient-reported outcomes with anatomical assessments provides a more accurate evaluation of surgical success in POP based on PFDI-20 and PFIQ-7 scores. Because POP is a multidimensional condition, assessing surgical outcomes requires a multimodal approach that considers symptom relief and QoL.